The effect of theory-based educational intervention on correct principles of manual material handling among men - Farough Mohammadian; Zahra Sadat Asadi; Mohsen Moradinia; Reza Tajik; Rasoul Abhar; Manijeh Soleimanifar (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Changing human behavior for the purposes of improving the way people work is an integral part of most educational interventions. This study aimed to evaluate the effect of a model based on the theory of planned behavior (TPB) on correct principles of manual material handling (MMH) among male soldiers. SUBJECTS AND METHODS: This study was a quasi-experimental, pretest-posttest research with a control group. Furthermore, 140 soldiers, from an area located in the city of Bandar Abbas, Iran, were selected through a simple random sampling and they were divided into two groups: intervention and control (70 subjects in each group). The data were collected using a three-part questionnaire including demographic information, the theory constructs, and MMH behavior. The intervention group was given the relevant education, and after 2 months, the both groups were evaluated. RESULTS: Based on regression analysis, attitude toward behavior and perceived behavioral control were predictors for correct principles of MMH. There were significant differences between the mean scores of the theory constructs before and after the education in intervention group (P < 0.001); however, no significant differences were observed in the theory constructs in the control group after the intervention. Before the education, the mean score of MMH of the intervention group was 38.30 ± 6.45; but after, the education, this changed into 44.20 ± 6.01, and significantly increased (P < 0.001). CONCLUSIONS: Educational intervention based on the TPB was effective in improving behavior for correct MMH in soldiers. Thus, the use of such educational programs according to the constructs of the planned behavior theory is recommended.